The shameful state - Sony Lab'Ou Tansi (Global African voices., 2015)
"Set in a fictitious African nation, this novel by the distinguished writer Sony Labou Tansi takes aim at the corruption, degeneracy, violence, and repression of political life in Africa. At the heart of The Shameful State is the story of Colonel Martillimi Lopez, the nation's president, whose eccentricity and whims epitomize the 'shameful situation in which humanity has elected to live.' Lopez stages a series of grotesque and barbaric events while his nation falls apart. Unable to resist the dictator's will, his desperate citizens are left with nothing but humiliation. The evocation of this deranged world is a showcase for the linguistic and stylistic inventiveness that are the hallmark of Sony Labou Tansi's work. This first English translation by Dominic Thomas includes a foreword by Congolese writer Alain Mabanckou that contextualizes the novel's importance in literary history and the significance of Sony Labou Tansi for future generations of writers."--Publisher summary